Absence of Mitochondrial Toxicity in Hearts of Transgenic Mice Treated with Abacavir - Kohler, James J. (Cardiovasc Toxicol, 2010)
Abacavir (ABC) is a guanosine nucleoside reverse transcriptase inhibitor (NRTI) with potent antiretroviral activity. Since NRTIs exhibit tissue-specific inhibition of mitochondrial DNA (mtDNA) synthesis, the ability of ABC to inhibit mtDNA synthesis in vivo was evaluated. Inbred wild-type (WT) and transgenic mice (TG) treated with ABC (3.125 mg/d p. o., 35 days) were used to define mitochondrial oxidative stress and cardiac function. Chosen TGs exhibited overexpression of HIV-1 viral proteins (NL4–3Δgag/pol, non-replication competent), hemizygous depletion or overexpression of mitochondrial superoxide dismutase (SOD2(+/−) knock-out (KO) or MnSOD OX, respectively), overexpression of mitochondrially targeted catalase (MCAT), or double “knockout” deletion of aldehyde dehydrogenase activity (ALDH2 KO). Impact on mtDNA synthesis was assessed by comparing changes in mtDNA abundance between ABC-treated and vehicle-treated WTs and TGs. No changes in mtDNA abundance occurred from ABC treatment in any mice, suggesting no inhibition of mtDNA synthesis. Left ventricle (LV) mass and LV end-diastolic dimension (LVEDD) were defined echocardiographically and remained unchanged as well. These results indicate that treatment with ABC has no visible cardiotoxicity in these adult mice exposed for 5 weeks compared to findings with other antiretroviral NRTI studies and support some claims for its relative safety.